Challenges in Statewide Implementation of a Prehospital Evidence-Based Guideline: An Assessment of Barriers and Enablers in Five States. (4th March 2019) - Adelgais, Kathleen M.; Sholl, J. Matthew; Alter, Rachael; Gurley, Kristin Lauria; Broadwater-Hollifield, Camille; Taillac, Peter
Abstract: Background: Individual states, regions, and local emergency medical service (EMS) agencies are responsible for the development and implementation of prehospital patient care protocols. Many states lack model prehospital guidelines for managing common conditions. Recently developed national evidence-based guidelines (EBGs) may address this gap. Barriers to statewide dissemination and implementation of model guidelines have not been studied. The objective of this study was to examine barriers and enablers to dissemination and implementation of an evidence-based guideline for traumatic pain management across 5 states.Methods: This study used mixed methods to evaluate the statewide dissemination and implementation of a prehospital EBG. The guideline provided pain assessment tools, recommended opiate medication dosing, and indications and contraindications for analgesia. Participating states were provided an implementation toolkit, standardized training materials, and a state-specific implementation plan. Outcomes were assessed via an electronic self-assessment tool in which states reported barriers and enablers to dissemination and implementation and information about changes in pain management practices in their states after implementation of the EBG.Results: Of the 5 participating states, 3 reported dissemination of the guideline, one through a state model guideline process and 2 through regional EMS systems. Two states did not disseminate or implement the guideline. Of these, one state chose to utilize a locally developed guideline, and the other state did not perform guideline dissemination at the state level. Barriers to state implementation were the lack of authority at the state level to mandate protocols, technical challenges with learning management systems, and inability to track and monitor training and implementation at the agency level. Enablers included having a state/regional EMS office champion and the availability of an implementation toolkit. No participating states demonstrated an increase in opioid delivery to patients during the study period.Conclusion: Statewide dissemination and implementation of an EBG is complex with many challenges. Future efforts should consider the advantages of having statewide model or mandatory guidelines and the value of local champions and be aware of the challenges of a statewide learning management system and of tracking the success of implementation efforts.